ANALYSIS OF THE IMPACT OF SOCIAL MEDIA DURING THE PANDEMIC ON THE MENTAL HEALTH OF ADOLESCENT DARUL ARQAM PUTRI ISLAMIC BOARDING SCHOOL - Azka Dhianti Putri (Study Program Guidance and Counseling, Univesitas Pendidik, 2021)
The Covid-19 pandemic has changed many things in our lives, one of which is the way we Social media is replaced by social media. Social media has becomes an integral part of a teenager. Because of course teenagers do their social activities with social media at this time. But social media certainly has a negative or positive impact. It depends on how wisely teenagers use social media. And this negative impact will certainly affect the mental health of teenagers. Even though during a pandemic, mental health is as important as physical health. Where adolescents in this period experience significant changes from psychology, physical, and social. So that requires them to constantly adapt to the environment. Therefore, of course it will be very dangerous if the mental health of adolescents is disturbed, because it will greatly affect their ability to adapt to the environment. This article discusses the analysis of the impact of social media during the pandemic on the mental health of the Darul Arqam Putri Islamic boarding school students who are currently still doing online learning at their respective homes. By using the literature study method and qualitative methods through interview techniques, it is hoped that it can provide a real picture of the mental health state of Darul Arqam students at this time.